The use of goat grazing for prevention of forest fires in the west Mediterranean Region of Turkey - Tolunay A.; Turkoglu T.; Kasikci D.; Daskiran I.; Ozmis M. (Pastoralism and sustainable development: proceedings, 2021)
In this study, the effects of goat grazing on reducing forest fires are investigated. For this purpose, trial areas were taken in 3 provinces (Antalya, Isparta and Burdur) within the study area which has rough terrain and scrubland. As a result of grazing goat flock in these areas, the amount of flammable material removed per unit area was calculated under 4 different intensities: weak grazing (70-100% of the total available aboveground biomass), medium grazing (70-40%), heavy grazing (40%-10%) and no grazing in the study area. The amount of flammable material removed by goat grazing in study areas where grazing is allowed in the state forests is annually -756,500 tons in Antalya Province, -304,000 tons in Isparta Province, -198,000 tons in Burdur Province and totally -1,258,500 tons in entire study area. Thus, goats remove the amount of flammable material from the Western Mediterranean Forests at the rate of 61%. Weak grazing (70-100%) in grazing classes cannot reduce the amount of flammable material. The grazing intensities that should be used to reduce the forest fire hazard are in medium grazing (70-40%) and heavy grazing (40-10%). The most suitable grazing period to preventing forest fires is the period between April 15 and June 15. Considering the presence of different forest vegetation in the study area, these grazing periods can be extended to 15 days earlier or 15 days later. Finally, the 3-month period between April 1 and June 30 is the most effective period of grazing for the prevention of forest fires.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)